Burden, emotional distress and quality of life among informal caregivers of lung cancer patients: An exploratory study. (18th April 2017) - Tan, J.‐Y.; Molassiotis, A.; Lloyd‐Williams, M.; Yorke, J.
Abstract : This study was conducted to explore the interrelationships among caregiver burden, emotional status and quality of life (QoL) in caregivers of lung cancer patients, and to identify whether caregiver burden and health status are associated with patient emotional status and QoL. Forty‐three dyads of lung cancer patients and their caregivers were included for analysis. Caregiver‐reported outcomes were measured by Caregiver Burden Scale (CBS), Caregivers Quality of Life Index‐Cancer (CQOLC) and Hospital Anxiety and Depression Scale (HADS), while patient‐reported outcomes were collected by HADS and Lung Cancer Symptom Scale (LCSS). The majority of the CBS and CQOLC scores were significantly higher in anxious and depressed caregivers than non‐anxious and non‐depressed caregivers ( p  <   .01 or .05). Caregivers of depressed patients experienced significantly greater emotional distress than those of non‐depressed patients ( p  <   .01). Significantly positive associations were identified among most of the CBS, CQOLC and caregiver HADS scores. Patient LCSS scores were positively correlated with the CBS and caregiver HADS scores, and patient HADS scores were also positively related to caregiver HADS scores. The close interrelationships between caregiver and patient health outcomes provide evidence that lung cancer patients and their caregivers should be viewed as a unit in future supportive service models.